The role of nociceptive neurons in allergic rhinitis - Cong, Jianchao; Lv, Hao; Xu, Yu (Frontiers in Immunology, 2024)
Allergic rhinitis (AR) is a chronic, non-infectious condition affecting the nasal mucosa, primarily mediated mainly by IgE. Recent studies reveal that AR is intricately associated not only with type 2 immunity but also with neuroimmunity. Nociceptive neurons, a subset of primary sensory neurons, are pivotal in detecting external nociceptive stimuli and modulating immune responses. This review examines nociceptive neuron receptors and elucidates how neuropeptides released by these neurons impact the immune system. Additionally, we summarise the role of immune cells and inflammatory mediators on nociceptive neurons. A comprehensive understanding of the dynamic interplay between nociceptive neurons and the immune system augments our understanding of the neuroimmune mechanisms underlying AR, thereby opening novel avenues for AR treatment modalities.